Quantum Treatment of Excitonic Energy Transfer in Photosynthesis - Haritha, A. (IISERM, 2018)
Energy transfer in light harvesting complexes of photosynthetic organisms shows quan- tum effects such as dephasing assisted transport and quantum coherence at room temperature. Engel et al. gave experimental proof of quantum coherence in Fenna- Matthews-Olson (FMO) complex of Green Sulfur bacteria. This system also shows high energy transfer efficiency. The mechanism behind this high efficiency is not com- pletely explained so far. In this thesis, we propose a new model to study the energy transfer dynamics of FMO-RC system. Along with molecular excitation, molecular vibrations are taken into account. We use Jaynes Cumming Hamiltonian to model the interaction between the electronic and vibrational states of the molecule. 40% efficiency is achieved in this model by incorporating a phononic bath in contact with the system.
Keywords: Photosynthesis; Solving Lindblad equation; Thermal state; Jaynes-Cummings Model